2020
DOI: 10.3390/cells9051224
|View full text |Cite
|
Sign up to set email alerts
|

M2 Macrophages Infiltrating Epithelial Ovarian Cancer Express MDR1: A Feature That May Account for the Poor Prognosis

Abstract: Multi drug resistance protein 1 (MDR1) expression on tumor cells has been widely investigated in context of drug resistance. However, the role of MDR1 on the immune cell infiltrate of solid tumors remains unknown. The aim of this study was to analyze the prognostic significance of a MDR1+ immune cell infiltrate in epithelial ovarian cancer (EOC) and to identify the MDR1+ leucocyte subpopulation. MDR1 expression was analyzed by immunohistochemistry in 156 EOC samples. In addition to MDR1+ cancer cells, we detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 38 publications
1
21
0
1
Order By: Relevance
“…Analysis of 53 breast cancers demonstrated the presence of this macrophage subtype in primary breast cancers and using the top nine differentially expressed genes by the MUC1-STinduced macrophages, we showed a significant association with poor prognosis. Interestingly, a recent paper has shown a significant correlation between 'cancer-associated MUC1' (a mixture of glycophenotypes) and macrophages when staining with CD163 46 . Our data indicate that at least one of the mechanisms whereby MUC1-ST can affect progression of cancers is by the direct induction of monocyte differentiation into macrophages with a TAM-like phenotype without the need for any additional factor.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of 53 breast cancers demonstrated the presence of this macrophage subtype in primary breast cancers and using the top nine differentially expressed genes by the MUC1-STinduced macrophages, we showed a significant association with poor prognosis. Interestingly, a recent paper has shown a significant correlation between 'cancer-associated MUC1' (a mixture of glycophenotypes) and macrophages when staining with CD163 46 . Our data indicate that at least one of the mechanisms whereby MUC1-ST can affect progression of cancers is by the direct induction of monocyte differentiation into macrophages with a TAM-like phenotype without the need for any additional factor.…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings have shown that immune cell infiltration is related to the prognosis of STAD [1,13]. A number of studies have shown that high infiltration of M2 macrophages indicates poor prognosis [1,[37][38][39]. In Cervical Cancer, FABP4 was considered to be correlated to immune cell infiltration [40].…”
Section: Discussionmentioning
confidence: 99%
“…This subset of macrophages often possess an anti-inflammatory phenotype and are in many studies identified using CD68, CD163, CD204 and/or CD206 as biomarkers [ 51 ]. Further, some TAMs also express multi drug resistance protein 1 supporting chemoresistance as demonstrated on CD163 + CD204 + TAMs in epithelial ovarian cancer [ 52 ]. However, the TAMs are not a homogenous subset of cells and they also encompass tumor-suppressive macrophages that instead prevent tumor growth and progression [ 49 , 50 ].…”
Section: Macrophages In Diseasementioning
confidence: 99%